An urgent referral strategy for symptomatic patients with suspected colorectal cancer based on a quantitative immunochemical faecal occult blood test. Issue 9 (September 2015) - Rodríguez-Alonso, Lorena; Rodríguez-Moranta, Francisco; Ruiz-Cerulla, Alexandra; Lobatón, Triana; Arajol, Clàudia; Binefa, Gemma; Moreno, Victor; Guardiola, Jordi
Abstract Background European health systems have developed referral guidelines for the selection of patients for the urgent investigation of suspected colorectal cancer. Aim To evaluate whether quantitative faecal immunochemical testing performs better than commonly used high-risk symptoms based strategies for fast-tracking cancer referrals. Methods We prospectively studied 1054 symptomatic patients referred for a colonoscopy who provided a sample for faecal immunochemical testing. The usefulness of faecal immunochemical testing and two current guidelines for urgent referral were compared for their efficacy in the detection of colorectal cancer and advanced neoplasia. Results The guidelines detected 46.7% and 43.3% of cases of colorectal cancer while faecal haemoglobin concentration ≥15 μg Hb/g detected 96.7% of cases. The diagnostic accuracy of both the guidelines and faecal haemoglobin concentration ≥15 μg Hb/g for the detection of advanced neoplasia was: sensitivity 38.3%, 36.1%, 57.1% and specificity 71.8%, 69.5%, 86.6%, respectively. Male gender (OR 2.35; p < 0.001), age (1.34; p = 0.002), and faecal haemoglobin concentration ≥10 μg Hb/g (7.81; p < 0.001) were independent predictive factors of advanced neoplasia. Conclusions A faecal immunochemical test based-strategy performs better than current high-risk symptoms based strategies for fast-tracking cancer referrals. A score that combines gender, age and a faecal immunochemical test could accurately estimate the risk of advanced neoplasia.